Chronic administration of a cannabis-derived mixture at an antihyperalgesic dose does not significantly enhance hepatotoxicity or the development of metabolic dysfunction-associated steatohepatitis in male mice - Kim B. Pedersen; Tomislav Jelesijevic; Tamara M. Morris; Sarah M. Melton; Ashley S. Henderson; John F. Glenn; Gregory J. Davenport; Martin J. J. Ronis; Peter J. Winsauer (Experimental Biology and Medicine)
Cannabis and cannabinoid mixtures have been linked to a variety of health benefits including pain mitigation, suppression of nausea produced by chemotherapeutic agents, anti-inflammatory effects, and effects on energy homeostasis, glucose, and lipid metabolism. The latter properties have led to the suggestion that these products could have therapeutic effects on the development of metabolic dysfunction-associated steatohepatitis (MASH) - a severe type of liver pathology in obese and diabetic patients. However, varying agonist and antagonistic properties of different cannabinoids on the endogenous cannabinoid system make prediction regarding hepatic effects and diet interactions difficult. The current study was designed to examine hepatic pathology following chronic administration of a cannabinoid mixture (NEPE14) at a dose equivalent to one previously demonstrating antihyperalgesic effects in rats. The effects of NEPE14 were investigated in a mouse model of MASH produced by feeding a Western diet rich in fat and simple sugars. After 24 weeks of NEPE14 administration, there was no hepatotoxicity in mice receiving the control diet and no significant exacerbation of MASH in mice receiving the Western diet. In conclusion, no chronic liver toxicity was observed, but there was also no evidence for protection against MASH by this product.